ASESMEN KOMPETENSI MINIMUM (AKM) KELAS SEKOLAH DASAR SEBAGAI SARANA EVALUASI KEMAMPUAN LITERASI DAN NUMERASI SISWA - Chesa, Nabilla; Binti Azizatun Nafi’ah (Jurnal Pendidikan Dasar, 2022)
Abstract: One of the government policies issued by the Ministry of Education and Culture to improve the quality of education in Indonesia is through the independent learning curriculum policy. This policy contains the main points of assessment which include literacy and numeracy. As is known, the pandemic has a significant impact on the quality of education in Indonesia, therefore in this policy the government holds a Asesmen Kompetensi Minimum (AKM) Kelas which is a tool that can be used by teachers in analyzing the learning outcomes of every student in elementary school. This is certainly important to know the competencies that students have after carrying out distance learning. This research uses quantitative research methods. The purpose of this study is to analyze and find out the results of the application of the Asesmen Kompetensi Minimum (AKM) Kelas. The results of this study are expected that based on the implementation of this program, it can help teachers to evaluate student learning outcomes and can make it easier for teachers to compile learning according to student needs based on the results of the assessment